Vicarious traumatization in the general public, members, and non-members of medical teams aiding in COVID-19 control - Li, Zhenyu; Ge, Jingwu; Yang, Meiling; Feng, Jianping; Qiao, Mei; Jiang, Riyue; Bi, Jiangjiang; Zhan, Gaofeng; Xu, Xiaolin; Wang, Long; Zhou, Qin; Zhou, Chenliang; et al. (Brain, behavior, and immunity, 2020)
•The vicarious traumatization scores for front-line nurses were significantly lower than those of non-front-line nurses;•The vicarious traumatization scores for the general public were significantly higher than those of front-line nurses.•Strategies that aim to prevent and treat vicarious traumatization in medical staff and general public are necessary. Since December 2019, more than 79,000 people have been diagnosed with infection of the Corona Virus Disease 2019 (COVID-19). A large number of medical staff was sent to Wuhan city and Hubei province to aid COVID-19 control. Psychological stress, especially vicarious traumatization caused by the COVID-19 pandemic, should not be ignored. To address this concern, the study employed a total of 214 general public and 526 nurses (i.e., 234 front-line nurses and 292 non-front-line nurses) to evaluate vicarious traumatization scores via a mobile app-based questionnaire. Front-line nurses are engaged in the process of providing care for patients with COVID-19. The results showed that the vicarious traumatization scores for front-line nurses including scores for physiological and psychological responses, were significantly lower than those of non-front-line nurses (P < 0.001). Interestingly, the vicarious traumatization scores of the general public were significantly higher than those of the front-line nurses (P < 0.001); however, no statistical difference was observed compared to the scores of non-front-line nurses (P > 0.05). Therefore, increased attention should be paid to the psychological problems of the medical staff, especially non-front-line nurses, and general public under the situation of the spread and control of COVID-19. Early strategies that aim to prevent and treat vicarious traumatization in medical staff and general public are extremely necessary.